HAYBOL: An Android-Based Apartment Locator Application - Consignado, Mark Lloyd Lester S; Velasco, Mark Lesther A; Sanvictores, Aladdin Paolo A; Jain, Archieval M; Balahadia, Francis F (International Journal of Computing Sciences Research, 2017)
Purpose – The study aims to develop a system for finding apartments and boarding houses named as HAYBOL. This android-based apartment locator application is a mobile one that can be used by the community especially students, easily find apartments and boarding houses as well as to help owners promote their businesses. Method – The proponents used Rapid Application Development (RAD) in developing the software which is a systems developmental method that follow phases such as requirement planning, user design, construction and cutover. Then, it also facilitated testing and evaluation, purposive sampling was used to select the respondents. Two sets of questionnaires were developed, one for the apartment and boarding house owners and another for the tenants. Results – Based on the result on the system evaluation using ISO 9126 in terms of functionality, usability, content, reliability and performance. Overall, the application was rated as 3.55 over which verbally-interpreted as excellent. Conclusion – The system meets its objective to provide access to the users an application for finding apartment in a convenient way. HAYBOL is well-commendable and accepted by the community which provides a better, easy way of advertising apartments and boarding houses, and reliable tool for finding nearby apartments and boarding houses. Recommendations – It recommends an expansion of the system coverage throughout the Laguna Province and to add a user guide and direction on the easiest ways to go to a chosen apartment to improve the effectiveness and functionality of the application. Research Implications – Real time apartment information is currently growing which much provides more good services to make renters life easier. Once mobile locator application has been established in the business will help users to personalize their search and reduce the amount of time wasted on a bad rental fit and assist to set a budget looking for apartment you can afford.